Antipati Digital dan Problem Kesantunan: Analisis Linguistik Forensik terhadap Komentar Instagram tentang Isu Dugaan Ijazah Palsu Joko Widodo - Hernita Syafri; Yarno; R. Panji Hermoyo (Universitas Muhammadiyah Makassar, 2026)
Digital public spaces have evolved into primary arenas for political discourse as well as for the expression of collective emotions. One prominent phenomenon is the proliferation of antipathy-laden comments on Instagram related to the alleged fake diploma issue of President Joko Widodo. This study aims to analyze forms of antipathy expressed in Instagram users’ comments from a forensic linguistics perspective and to examine associated violations of language politeness principles. Employing a qualitative descriptive approach, the data consist of 58 Instagram comments collected from posts by public figures and online news media during May–June 2025. Data were analyzed through stages of reduction, classification, and linguistic interpretation based on forensic linguistics frameworks and Brown and Levinson’s politeness theory. The findings reveal that antipathy is predominantly expressed through hate speech, sarcasm, insults, unsubstantiated accusations, harsh satire, and negative labeling. From a forensic linguistics perspective, these expressions are characterized by negative evaluative lexis, presuppositions that frame assumptions as facts, and delegitimizing linguistic strategies targeting the subject. In terms of politeness, most comments violate both positive and negative face, indicating potential ethical and legal implications. This study underscores the urgency of language politeness education as an integral component of digital literacy in fostering responsible online public discourse. Keywords: forensic linguistics, antipathy expressions, language politeness, Instagram, digital public space